Prognostic Implications of a Morphometric Evaluation for Chronic Changes on All Diagnostic Native Kidney Biopsies. Issue 10 (October 2022) - Denic, Aleksandar; Bogojevic, Marija; Mullan, Aidan F.; Sabov, Moldovan; Asghar, Muhammad S.; Sethi, Sanjeev; Smith, Maxwell L.; Fervenza, Fernando C.; Glassock, Richard J.; Hommos, Musab S.; Rule, Andrew D.
Significance Statement: Routine clinical review of native kidney biopsies includes semiquantitative visually estimated degree of sclerosis of glomeruli, tubules, interstitium, and arteries. The authors evaluated morphometric measures of sclerosis and nephron size and investigated how they can be used to improve the prediction of progressive CKD and ESKD. Visual estimates made by pathologists versus morphometric measures of percentages of global glomerulosclerosis, interstitial fibrosis and tubular atrophy (IFTA), and arteriosclerosis produced similar predictions of outcomes. However, additional morphometric measures of percentage of glomerulosclerosis (percentage of ischemic-appearing, segmentally, or globally sclerosed glomeruli), IFTA foci density, and detection of any arteriolar hyalinosis improved prediction of both outcomes. A modified renal chronicity score including these new morphometric measures improved risk estimation for ESKD or progressive CKD. Visual Abstract: Abstract : Background: Semiquantitative visual inspection for glomerulosclerosis, interstitial fibrosis, and arteriosclerosis is often used to assess chronic changes in native kidney biopsies. Morphometric evaluation of these and other chronic changes may improve the prognostic assessment. Methods: We studied a historical cohort of patients who underwent a native kidney biopsy between 1993 and 2015 and were followed through 2021 for ESKD and for progressive CKD (defined as experiencing 50% eGFR decline, temporary dialysis, or ESKD). Pathologist scores for the percentages of globally sclerosed glomeruli (GSG), interstitial fibrosis and tubular atrophy (IFTA), and arteriosclerosis (luminal stenosis) were available. We scanned biopsy sections into high-resolution images to trace microstructures. Morphometry measures were percentage of GSG; percentage of glomerulosclerosis (percentage of GSG, ischemic-appearing glomeruli, or segmentally sclerosed glomeruli); percentage of IFTA; IFTA foci density; percentage of artery luminal stenosis; arteriolar hyalinosis counts; and measures of nephron size. Models assessed risk of ESKD or progressive CKD with biopsy measures adjusted for age, hypertension, diabetes, body mass index, eGFR, and proteinuria. Results: Of 353 patients (followed for a median 7.5 years), 75 developed ESKD and 139 experienced progressive CKD events. Visually estimated scores by pathologists versus morphometry measures for percentages of GSG, IFTA, and luminal stenosis did not substantively differ in predicting outcomes. However, adding percentage of glomerulosclerosis, IFTA foci density, and arteriolar hyalinosis improved outcome prediction. A 10-point score using percentage of glomerulosclerosis, percentage of IFTA, IFTA foci density, and any arteriolar hyalinosis outperformed a 10-point score based on percentages of GSG, IFTA, and luminal stenosis >50% in discriminating risk of ESKD or progressive CKD. Conclusion: Morphometric characterization of glomerulosclerosis, IFTA, and arteriolar hyalinosis on kidney biopsy improves prediction of long-term kidney outcomes.